PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN MAHASISWA FAKULTAS EKONOMI ANGKATAN 2014-2016 UNIVERSITAS ISLAM MALANG - Fuji Santoso; Rois Arifin; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
AbstractThe purpose of this study is to know and analyze how the Influence ofService Quality And Facilities To Student Satisfaction Faculty of EconomicsAngakatan 2014-2016 Islamic University of Malang. The population in this studyis all students of the Faculty of Economics UNISMA. This research used surveymethod by taking sample from a population and using questionnaire as main datacollecting tool, with number 95 respondents. Analytical techniques in this studyusing multiple linear regression.The results showed that partially Variable Service Quality and Facilitieshave a positive and significant effect on Student Satisfaction. While simultaneously that Variable Service Quality and Facility Variable have positive and significanteffect to Student Satisfaction Variables.Keywords: Service Kuliah, Facilities, and Student Satisfaction